2016
DOI: 10.1080/21641846.2015.1124520
|View full text |Cite
|
Sign up to set email alerts
|

Case definitions integrating empiric and consensus perspectives

Abstract: Background There has been considerable controversy regarding how to name and define the illnesses known as myalgic encephalomyelitis (ME) and chronic fatigue syndrome (CFS). The IOM report has proposed a new clinical criteria and name for this illness, but aspects of these recommendations have been scrutinized by patients and scientists. Purpose It is possible that both empiric and consensus approaches could be used to help settle some of these diagnostic challenges. Using patient samples collected in the Un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 51 publications
(81 reference statements)
1
8
0
Order By: Relevance
“…Patients with ME had a significantly higher CDC, CFS and CDC rest symptom scores than the patients with CFS and atypical ME. This is in line with previous studies of Jason et al[56] [57] suggesting that CFS and ME are not different but merely are a continuum in disease severity expression.However, more importantly, the favorable effects of curcumin are both present in CFS and in ME patients.…”
supporting
confidence: 93%
“…Patients with ME had a significantly higher CDC, CFS and CDC rest symptom scores than the patients with CFS and atypical ME. This is in line with previous studies of Jason et al[56] [57] suggesting that CFS and ME are not different but merely are a continuum in disease severity expression.However, more importantly, the favorable effects of curcumin are both present in CFS and in ME patients.…”
supporting
confidence: 93%
“…[8,19,20,21,22] In the present study, it was found that Role-Physical and Social Functioning were significantly correlated to both the current hours and percent reduction in hours spent on different activities. These findings demonstrate that as current hours decrease and percent reduction in hours increases, the scores on the Role-Physical and Social Functioning scales will decrease, indicating worse functioning.…”
Section: Discussionmentioning
confidence: 64%
“…Symptom frequency and severity were converted to a 100-point scale, and were averaged to create one composite score for each symptom. Symptoms were compiled into domains [23] based on symptomology suggested by the Canadian Clinical Criteria for ME/CFS [2] and select other symptoms categories that were empirically identified through factor analysis [23,2,7]. The domain composite scores were calculated by converting the frequency and severity for each symptom in the domain and averaging them to create one score.…”
Section: Methodsmentioning
confidence: 99%